Evidence for an alpha 2-macroglobulin with complement-inhibiting activity in rat serum. - Bellott, R. (1991)
alpha 2-Macroglobulin (alpha 2M) was purified both from the serum of male rats developing an acute turpentine-induced inflammatory reaction where its concentration is greatly increased (3-4 mg/ml) and from the serum of healthy males where it is present at low levels (15-30 micrograms/ml). A three-step purification procedure involving gel filtration, anion exchange chromatography on DEAE cellulose and negative immunoaffinity was used. A pure native alpha 2M, as assessed by biochemical and immunological tests, was obtained. This alpha 2M differed from other subforms in terms of its electric charge and its complement-inhibiting activity in a complement-dependent immune haemolysis test. Moreover, this inhibitory activity was not affected by complexing with trypsin or modification by interaction with methylamine showing that this newly described property is not linked to the well known antiproteinase function of alpha 2M.